The Use of Medicinal Plants Among the Community of Blangjerango, Gayo Lues Regency - Br. Panjaitan, Putri Pahiza; Ahadi, Rizky; Amin, Nurdin; Eriawati, Eriawati; Rahmawati, Lina (Jurnal Biologi Tropis, 2026)
Traditional knowledge regarding medicinal plants in Blangjerango District, Gayo Lues Regency, is increasingly threatened by modernization and the growing preference for modern medicine among younger generations. This study aimed to identify medicinal plant species used by the community, document the plant parts utilized, preparation methods, and their medicinal benefits. The study utilized a qualitative descriptive framework combined with an ethnobotanical perspective. Information was gathered via on-site observations, thorough interviews, record keeping, and Participatory Rural Appraisal (PRA) that engaged local residents, traditional healthcare practitioners, and senior community members. The research identified 13 species of medicinal plants belonging to different families that are employed to address health issues like fever, coughing, wounds, high blood pressure, digestive problems, and skin ailments. The leaves emerged as the most commonly used part of the plants, while methods of preparation involved boiling, grinding, incinerating, and applying directly. The findings indicate that medicinal plants remain an important component of traditional healthcare practices in Blangjerango; however, knowledge of their use is predominantly retained by older generations, with declining interest among younger people. Therefore, documentation and preservation of ethnobotanical knowledge are essential to support biodiversity conservation and safeguard local cultural heritage. Collaboration between educational institutions and local governments is recommended to promote the transmission of traditional medicinal plant knowledge to younger generations.